Molecular Pathways Mediating Immunosuppression in Response to Prolonged Intensive Physical Training, Low-Energy Availability, and Intensive Weight Loss - Sarin, Heikki V.; Gudelj, Ivan; Honkanen, Jarno; Ihalainen, Johanna K.; Vuorela, Arja; Lee, Joseph H.; Jin, Zhenzhen; Terwilliger, Joseph D.; Isola, Ville; Ahtiainen, Juha P.; Häkkinen, Keijo; Jurić, Julija; et al. (Frontiers in Immunology, 2019)
Exercise and exercise-induced weight loss have a beneficial effect on overall health, including positive effects on molecular pathways associated with immune function, especially in overweight individuals. However, prolonged intense exercise training periods without sufficient recovery and energy intake aiming to accomplish very low levels of body fat may lead to temporary immunodepression. Here, we applied a high-throughput systems biology approach to better characterize potential key pathways associated with immune system modulation during intensive weight loss and subsequent weight regain. We examined 42 healthy female physique athletes (age 27.5±4.0 years, body mass index 23.4±1.7 kg/m2) volunteered into either a diet group (n=25) or a control group (n=17). For the diet group, the energy intake was reduced and exercise levels were increased to induce loss of fat mass that was subsequently regained during a recovery period. The control group was instructed to maintain their typical lifestyle, exercise levels, and energy intake at a constant level. For quantification of systems biology markers, fasting blood samples were drawn at three time points: baseline (PRE), at the end of the weight loss period (MID 21.1±3.1 weeks after PRE), and at the end of the weight regain period (POST 18.4±2.9 weeks after MID). In contrast to the control group, the diet group showed significant (false discovery rate <0.05) alteration of all measured immune function parameters – white blood cells, immunoglobulin G glycome, transcriptome, and cytokine profile. Integrative omics revealed effects on multiple levels of immune system as dysregulated haematopoiesis, suppressed immune cell proliferation, and loss of immune cell function by reduced antibody and chemokine secretion was detected after intense weight loss. During the weight regain period, the majority of the measured immune function parameters returned back to the baseline. In summary, this study elucidated a number of molecular pathways presumably explaining immunosuppression in individuals going through prolonged periods of intense training with low-energy availability. Our findings also reinforce the perception that the way in which weight loss is achieved (i.e., dietary restriction, exercise, or both) has a distinct effect on how the immune system is modulated.